Determination of the distorted surface layer thickness in machined optically transparent polymer articles - Khlapova, N.P.; Litvinenko, M.V.; Chernyshev, A.A. (Functional Materials, 2004)
The functional performance of the optical polymer articles and the service life thereof are defined to a considerable extent by the surface layer state. When machined, the surface layer of polymer articles differs in its properties from the initial material. The combined force and heat action during the cutting results in a complex final structure state of the surface layer. This fact requires investigations to determine the changed (distorted) layer depth after the machining and to study its influence on the functional properties of the optical polymer articles. Функциональные свойства и долговечность работы изделий из оптических полимеров в значительной степени определяются состоянием их поверхностного слоя. При механической обработке поверхностный слой полимерных изделий приобретает свойства, отличные от свойств исходного материала. Взаимное проявление силового и теплового факторов в процессе резания приводит к сложному итоговому структурному состоянию поверхностного слоя изделия. Это требует проведения обстоятельных исследований для выявления глубины измененного (нарушенного) слоя после механической обработки и изучения его влияния на эксплуатационные свойства оптических полимерных изделий. Функціональні властивості і довговічність роботи виро6ів з оптичних полімерів в значній мірі визначаються станом їхнього поверхневого шару. При механічній обробці поверхневий шар полімерних виробів здобуває властивості, відмінні від властивостей вихідного матеріалу. Взаємний прояв силового і теплового факторів у процесі різання приводить до складного підсумкового структурного стану поверхневого шару виробу. Це вимагає проведення докладних досліджень для виявлення глибини зміненого (порушеного) шару після механічної обробки і вивчення його впливу на експлуатаційні властивості оптичних полімерних виробів.